Indium Imidazo[4,5,-b]porphyrins as Photocatalysts for Oxidation of Sulfides - Inna A. Abdulaeva; Mikhail A. Filatov; Azhar Kechiche; Alla Bessmertnykh-Lemeune (Molecules)
Over the past two decades, the application of photocatalytic reactions in organic synthesis has increased remarkably. Porphyrins, renowned for their exceptional photophysical properties, photostability, and prevalence in natural catalytic processes, are attracting significant attention as promising photocatalysts for reactions proceeding through energy transfer and one-electron transfer. In this work, we synthesized the indium(III) complex of 2-[4-(diethoxyphosphoryl)phenyl]-1H-imidazo[4,5-b]-5,10,15,20-tetramesitylporphyrin (InTMPIP) and explored its application as a photocatalyst for the oxidation of sulfides by dioxygen or air. Complex InTMPIP was found to generate singlet oxygen with quantum yield of 0.92 (toluene) and enables efficient photooxidation of sulfides to sulfoxides by dioxygen in “green” acetonitrile/water (4:1 v/v) or methanol/chloroform (2:1 v/v) solvent mixtures with almost quantitative yield. Furthermore, InTMPIP was grafted onto hydrated mesoporous titania and materials InTMPIP/TiO2-1 and InTMPIP/TiO2-2 with different In/Ti ratios were obtained and investigated. The composition and structure of the materials were studied using a combination of elemental analysis, various spectroscopic methods, gas adsorption measurements, and SEM imaging. Finally, the photocatalytic efficiency of InTMPIP/TiO2-2 was explored in aerobic photooxidation of sulfides. The heterogenized complex enables selective synthesis of sulfoxides under “green” conditions; however, it is prone to leaching into the solution when irradiated with both blue and red LEDs.